El Camino Real de California : From Ancient Pathways to Modern Byways - Sánchez, Joseph P. (Book collections on Project MUSE., 2019)
"The arrival of Spaniards in 1769 served as a defining moment for California's future. They described the First Peoples and their cultures and provided a window into the evolution of California's Camino Real. In an effort to establish the Camino Real de California as a UNESCO World Heritage Site, Joseph P. Sánchez explores the rich history of the path running from San Diego to San Francisco in this significant study. While records capture the stories and legends of the Camino Real there is little information on the exact ground route. Sánchez utilizes historical and archaeological literature and the documentation from Spanish and Mexican archives to begin the much-needed process of authentication of this braided corridor to further establish the Camino Real de California's integrity and valuable history, which is shared with Spain, Mexico, and Native American tribes. Their story is part of the patrimony of the Camino Real de California, which ought to be authenticated, preserved, and protected for future generations to enjoy."--